ELT Classroom Management Strategies: A Case of Grade Eight in Nepalese Schools - Banstola, Pitri Raj (Journal of NELTA Gandaki, 2024)
Managing the classroom is one of the responsibilities of a school teacher. A well-managed classroom enhances English language teaching and learning. However, the trend of ELT classroom management in Nepalese schools is still unresearched. Therefore, the paper aims to explore the ELT classroom management strategies in grade eight of Neplease Schools. Following an ethnographical design under a qualitative research approach and involving students and teachers of nine English classes of grade eight from eight schools in Pokhara city as the participants, I collected qualitative information through observation, interview, and FGD. The findings reveal that teachers attempt to manage their classrooms variously. However, classroom management is still incomplete. Instead of formulating new strategies, the rooms are traditionally organised, and the seats are arranged in orderly rows. The teachers follow unauthentic materials as the textbooks, use usual materials and apply lecture techniques for all the lessons. Teachers, educators, school administration, and policymakers should formulate new strategies for managing English classrooms.